Antifatigue Effect of Panax Notoginseng Leaves Fermented With Microorganisms: In-vitro and In-vivo Evaluation - Yang, Min; Tao, Liang; Zhao, Cun-Chao; Wang, Zi-Lin; Yu, Zhi-Jin; Zhou, Wen; Wen, Yan-Long; Li, Ling-Fei; Tian, Yang; Sheng, Jun (Frontiers in Nutrition, 2022)
Fatigue is a common physiological phenomenon caused by many complicated factors. Excessive fatigue will lead to a series of uncomfortable reactions and damage body health. Panax notoginseng leaves (PNL) is a new resource food that good for soothing nerves, nourishing the heart and strengthening the spleen. Microbial fermentation could increase the content of bio ingredients and produce new active ingredients. However, the effect of fermented P. notoginseng leaves (FPNL) on antifatigue and the molecular mechanisms remain to be elucidated. Thus, in this study, we evaluated the antifatigue effect of co-fermented P. notoginseng leaves by Saccharomyces cerevisiae and Bacillus subtilis in vitro and in vivo, and its mechanism was further elucidated. The results showed that FPNL exhibited higher saponins, organic phenolic acids content, and antioxidant activity than PNL. FPNL improved ISO-induced H9c2 myocardial cell damage by alleviating apoptosis (modulating Bax and Bcl-2 protein expression) and reducing antioxidants in vitro. Moreover, in vivo experiment showed that FPNL significantly prolonged the weight-loading swimming time of mice. After gavaged FPNL, the levels of liver glycogen and serum lactate dehydrogenase activity were increased in mice. In contrast, the levels of blood urea nitrogen, lactate acid, and malondialdehyde were decreased. In summary, our results indicated that FPNL showed a good antifatigue effect in vivo and in vitro.